In-vitro reconstitution of telomeric chromatin - Wong, Sook Yi (2016)
Telomere is a region, situated at the ends of all eukaryotic linear chromosomes, consisting of a repetitive sequence of TTAGGG in vertebrates. It has a protective role in maintaining chromosomal stability and integrity, by conferring protection against DNA damage response and chromosomal abnormality. Structurally, telomere is featured with shelterin complex, single stranded G-rich sequence and nucleosome. However, little is known about the telomeric nucleosome due to the nucleosome-disfavoring property of telomeric DNA that induces high energy cost on telomeric nucleosome formation. In this study, we aim to reconstitute telomeric nucleosome array in-vitro, using human histone octamer and telomeric DNA to investigate on the biochemical and biophysical properties of telomeric chromatin. Specifically, my project began with material preparation for the reconstitution, namely: (1) expression and purification of Histone 4, (2) Histone Octamer refolding and (3) amplification and purification optimization of telomeric DNA. In this study, preliminary reconstitutions were performed and studied using Electrophoretic Mobility Shift Assay and Atomic Force Microscopy. However, refinement in the quality of the materials and reconstitution of telomeric nucleosome array are still required to prevent interference during the investigation on the biochemical and biophysical properties of the telomeric chromatin.